Associations Between Autoimmune Conditions and Gastric Cancer Risk Among Elderly Adults in the United States. (31st March 2022) - Song, Minkyo; Camargo, M. Constanza; Derkach, Andriy; Rabkin, Charles S.; Engels, Eric A.
Abstract : INTRODUCTION: Pernicious anemia (PA) is a risk factor for gastric cancer. Other autoimmune conditions may also contribute. METHODS: In a case-control study, we evaluated 47 autoimmune conditions among 39, 125 gastric cancers and 200, 000 cancer-free controls. RESULTS: Six conditions were associated with increased gastric cancer risk (range of adjusted odds ratios: 1.28–1.93, P < 0.05): PA, membranous nephropathy, primary biliary cirrhosis, pure red cell aplasia, primary sclerosing cholangitis, and Graves disease. PA was associated with 8 other autoimmune conditions (adjusted odds ratios: 1.57–4.54, P < 0.05). DISCUSSION: Autoimmune conditions associated with gastric cancer or PA may reflect effects of autoimmune gastritis or other carcinogenic pathways.